The Latest Trends in Sleep Medicine - H. Iftikhar, Imran; I. Musani, Ali (Bentham Science Publishers, 2022)
The field of sleep medicine has gone through tremendous evolution since the discovery of REM sleep in 1953 and remarkable research in recent years has led to multiple advances in sleep medicine. Approvals for new medicines for treating sleep disorders along with new evidence-based interventions for insomnia and sleep apnea, have transformed sleep medicine into a medical specialty in its own right.The Latest Trends in Sleep Medicine reviews the most important improvements in sleep medicine, with contributions from over fifteen international and respected experts in the discipline. Ten chapters cover topics of interest to healthcare professionals who are focused on somnology such as the management of sleep disorders, restless leg syndrome, sleep apnea medication and surgery, REM sleep behavior disorder and cognitive behavioral therapy for insomnia. In addition to these topics in medicine, the contributors present broader picture of sleep medicine by reviewing secondary topics such as sleep and aging, and driving safety.The Latest Trends in Sleep Medicine will be useful to healthcare professionals seeking to improve their understanding about contemporary sleep medicine. It also serves as a timely update for respiratory and sleep medicine clinicians, whose efforts are still needed in treating and improving the quality and length of life in patients with complex sleep disorders.Audience:Healthcare professionals, residents and students in general, respiratory and sleep medicine sub specialties.